RESEARCH ON THE SUCCESSFUL LEVEL OF THE STATE'S ROLE IN VIETNAM'S TOURISM DEVELOPMENT AFTER FORMING THE ASEAN ECONOMIC COMMUNITY (AEC) - Nguyễn, Thị Anh Tuyết (Finance Publishing House, 2023)
At the scene of forming the ASEAN Economic Community (AEC), the State plays a vital role in developing Vietnam's tourism. The State has many mechanisms and policies to encourage and facilitate Vietnam's tourism to develop. However, large numbers of policies and laws on tourism are still lacking and inconsistent, not really clear, and not effective: some regulations are not suitable; Legal documents are promulgated slowly compared to requirements, with low effectiveness and efficiency. Through a survey sent to 112 tourism businesses in the area of Hanoi, Da Nang, Ho Chi Minh City, and 108 managers at all levels, this research determined; to evaluate the success factor of the state's role in tourism development in Vietnam after the AEC was formed. On that basis, the research contributes to theoretically clarifying the state's role in tourism development in Vietnam after the AEC was formed.